Myocardial Cut-off Sign is a Sensitive and Specific Cardiac Computed Tomography and Magnetic Resonance Imaging Sign to Distinguish Left Ventricular Pseudoaneurysms From True Aneurysms. Issue 1 (January 2022) - Ballard, David H.; Jokerst, Clinton; Raptis, Constantine A.; Pilgram, Thomas K.; Woodard, Pamela K.
Abstract : Purpose: The purpose of this study was to describe the myocardial cut-off sign, assess its ability to distinguish left ventricular pseudoaneurysms (LV PSAs) from true aneurysms (LVAs), and compare its performance with other imaging findings and quantitative measurements used to differentiate LV PSAs from LVAs. Materials and Methods: This retrospective single-center study identified patients with preoperative cardiac computed tomography (CT) or magnetic resonance imaging (MRI) and surgically confirmed LVAs or LV PSAs over a 10-year period. Seventeen LV PSAs (11 MRI, 6 CT) and 18 LVAs (10 MRI, 8 CT) were included. The myocardial cut-off sign was objectively a >50% decrease in aneurysm sac wall thickness measured at 1 cm from the aneurysmal neck (measurements at 2 cm were also assessed) and subjectively an abrupt "cut-off" of myocardium for the aneurysm sac for PSA compared with a gradual tapering of sac wall thickness for LVA. Two radiologists independently evaluated images for the subjective presence of this sign. Results: The myocardial cut-off sign was 91% sensitive and 97% specific when measured 1 cm from the aneurysm neck. When measured at 2 cm from the neck, the sign was 100% sensitive and 69% specific. Subjective analysis of whether the myocardium appeared "cut-off" was 94% to 100% sensitive and 78% to 94% specific with excellent agreement for both PSA (κ=0.94) and LVA (κ=0.83). Conclusions: The myocardial cut-off sign on cardiac CT and MRI is a sensitive and specific finding of LV PSA. Specificity is improved with objective measurements compared with subjective assessment (97% vs. 78% to 94%). This sign may help radiologists distinguish between LV PSAs and LVAs. Abstract : Supplemental Digital Content is available in the text.